Comparing the effectiveness of Zekr therapy in Islam with mindfulness therapy on anxiety and life expectancy of mothers with mentally disabled children - Esmailim Dehkhajeh, Masuomeh; Fallah, Mohammad Hossain; Vaziri , Saeed; Asi Mozneb, Abolghasem (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this research was to compare the effectiveness of Zekr therapy in Islam with mindfulness therapy on anxiety and life expectancy of mothers with mentally disabled children in Meybod city. Method: The design of the present research was applied in terms of its purpose and the method of conducting it was quasi-experimental with a pre-test and post-test design with two experimental groups and one control group. The statistical population of the research is all mothers with mentally disabled children in Meybod city. Among the statistical population, 45 mothers with intellectually disabled children were selected in a targeted and available manner and randomly divided into three groups in the form of two groups of 15 experimental people (30 people) and control group (15 people). Beck’s anxiety questionnaire was used to collect and measure mothers’ anxiety, and mothers’ life expectancy was measured with Snyder et al.’s questionnaire. Then exercise protocols (remembering therapy and mindfulness) were implemented. To answer the research hypotheses, the covariance tests were performed at the five percent error level using SPSS software version 26. Results: The results of covariance analysis for mindfulness treatment showed that 62.2% of life expectancy scores of mothers with intellectually disabled children are explained. Also, 55.6% of the anxiety scores of mothers with mentally retarded children are explained based on the mindfulness model. Also, 59.9% of Zekr therapy protocol scores are explained on the variable of life expectancy of mothers with mentally retarded children. Finally, according to the eta squared value (0.746), 74.6% of the scores of the Zekr therapy protocol are explained on the variable of anxiety of mothers with mentally retarded children. From the analysis of Shefe’s follow-up test, it can be concluded that the mean of anxiety in the dhikr therapy and mindfulness group has decreased significantly compared to the control group, but the two experimental groups have no significant difference from each other (α=0.05). It can also be concluded that the average life expectancy in the Zekr therapy and mindfulness group has decreased significantly compared to the control group, but the two experimental groups have no significant difference from each other (α=0.05). Conclusion: The obtained results indicated that both the mentioned treatment courses were equally effective in reducing anxiety and increasing the life expectancy of mothers with mentally disabled children.